2021
DOI: 10.1017/aae.2021.3
|View full text |Cite
|
Sign up to set email alerts
|

Change in Hay-to-Milk Price Responsiveness with Dairy Industry Expansion

Abstract: The dairy industries in California, Idaho, and New Mexico expanded rapidly during the early 2000s. This study focuses on the expansion effects on milk-to-hay price responsiveness. Dairy industry expansion makes hay markets tighter, with less available marketable supply in most periods. The empirical models account for the expansion effect as well as those from hay exports and low stocks-to-use ratios that also cause changes in hay market demand characteristics. The results show that hay-to-milk price responsiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…The timely flow of price information between markets can help speed price transmission (Hatzenbuehler et al, 2021). Mishra and Kumar (2011) tested the integration of different vegetable markets in Nepal and concluded that improving market information is essential to increasing their efficiency.…”
Section: Price Transmissionmentioning
confidence: 99%
“…The timely flow of price information between markets can help speed price transmission (Hatzenbuehler et al, 2021). Mishra and Kumar (2011) tested the integration of different vegetable markets in Nepal and concluded that improving market information is essential to increasing their efficiency.…”
Section: Price Transmissionmentioning
confidence: 99%